STUDI EKSPERIMENTAL PENGARUH PERUBAHAN NILAI KADAR AIR TANAH TERHADAP NILAI CBR (CALIFORNIA BEARING RATIO) - Pratama, Ricky Yuda; Minaka, Utari Sriwijaya; Devi, Debby Sinta (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
Soil water content significantly influences the bearing capacity of a soil. Bearing capacity is the ability of the soil to support construction loads. In a construction project, the subgrade must be able to support the planned loads and meet the requirements for successful construction. This experimental study aimed to determine the soil type, specific gravity, plasticity index, and the effect of changes in soil water content on the CBR values ​​of soaked and unsoaked soil from Lubuk Mumpo Village, Gunung Megang District, Muara Enim Regency. This study involved mixing native soil with mixture percentages of -10% OMC, -20% OMC, and +10% OMC, +20% OMC, to determine the CBR value. Ten soil samples were prepared for this test: 5 unsoaked and 5 soaked samples, based on SNI 1744-2012. The highest CBR values ​​were obtained at 10.94% for the -20% soaking variation (soaked) for 4 days and 5.33% for the -20% unsoaked variation (unsoaked) compared to the original soil. These results indicate that a 20% decrease in water content below the OMC increases the CBR value, while an increase in water content above the OMC decreases the CBR value.